Chemical deposition of La0.7Ca0.3MnO3±δ films on ceramic substrates - Morilla-Santos, Cássio [UNESP]; Schreiner, Wido Herwig; Lisboa Filho, Paulo Noronha [UNESP] (ABM, ABC, ABPol, 2011)
In this paper, it is reported the growth of La0.7Ca0.3MnO3±δ films using a chemical solution deposition method (CSD) by the spin-coating technique. Such solution was prepared through a route based on modified polymeric precursor method. Spin-coating deposition on different ceramic substrates was performed and analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS). The magnetic response of the prepared specimens was studied using a SQUID magnetometer. The obtained results indicated uniform deposition on SrTiO3 and LaAlO3 substrates with similar characteristics. Furthermore, significant differences were detected in the Mn3+/Mn4+ valence ratio and a corresponding diverse magnetic response was observed. The sample prepared on SrTiO3 and LaAlO3 presented a critical temperature around 270 K as expected.
Keywords: chemical solution deposition; Pechini method; spin-coating; magnetic material